Improved energy recovery through novel flow injection on a mixed flow turbine - Liu, Hao (Nanyang Technological University, 2020)
Secondary flow injection is a way which allows for the efficiency of turbomachinery to be increased. In this thesis, a novel method for improving turbine performance using secondary flow injection through an injection slot over the turbine shroud is investigated. Numerical simulations were conducted on a mixed flow turbocharger turbine to test the effectiveness of secondary flow injection. Preliminary single passage simulations show that while injection was able to improve turbine blade loading and power by strengthening the tip leakage vortex, efficiency gains were minimal. The initial simulations also found that injection velocity and yaw angle were important parameters that affect turbine performance. An optimization was performed at the peak efficiency operating point at 50% turbine design speed to determine the injection set up which gives the highest turbine efficiency. The final optimized point resulted in an efficiency increase of 2.6 percentage points compared to the baseline scenario. Flow analysis shows that injection partially blocks the flow passage near the blade tip, forcing turbine passage flow to migrate towards the hub. This apparently weakens the hub suction side separation vortex and reduces entropy generation from the vortex. Using results from the optimization, a prototype was built. Experimental testing of the prototype was conducted and validated against full stage turbine CFD simulation results. Full stage turbine CFD results show that with inlet nozzle vanes, secondary flow injection did not result in any visible improvement in the internal flow field and entropy generation, but for an ideal injection overall efficiency can be improved by up to 2.28 percentage points at a velocity ratio of 0.75. Without nozzle vanes, however, secondary flow injection resulted in an efficiency improvement of up to 6.79 percentage points by weakening the hub suction side separation vortex and reducing its associated losses. Injection on the vaneless turbine configuration also resulted in a roughly 2 percentage point improvement in the peak turbine efficiency over the vaned turbine configuration. This might be due to more flow energy available to be extracted by the rotor from reduced losses due to the lack of nozzle vanes. Finally, a re-optimization of the injection was conducted by using the rotor inlet velocity profiles obtained from the full stage vaned turbine simulations as inlet boundary conditions on a single passage domain. Results from the re-optimization show that at VR higher than the peak efficiency point, the injected flow has reduced the entropy generation near the tip gap by disrupting the formation of the tip leakage vortex. However, at VR near or below the peak efficiency point there is no clear efficiency improvement from flow injection. The maximum efficiency obtained was 2.71 percentage points. Overall, the research has shown that secondary flow injection has potential to increase turbine performance under some operating conditions.